Antimicrobial resistance and genetic diversity of Salmonella Infantis isolated from foods and human samples in Morocco. (September 2018) - Ed-Dra, Abdelaziz; Karraouan, Bouchra; Allaoui, Abdellah El; Khayatti, Meriem; Ossmani, Hicham El; Filali, Fouzia Rhazi; ElMdaghri, Naima; Bouchrif, Brahim
Highlights: 84.6% (22/26) of Salmonella Infantis strains were susceptible to all antimicrobials tested. Two strains of Salmonella Infantis were positive for the bla TEM gene. One strain of Salmonella Infantis was positive for intI1 and class 1 integron. PFGE analysis of the 26 Salmonella Infantis strains gave five different pulsotypes. Abstract: Objectives: Genotyping of Salmonella strains is an important molecular tool to discriminate isolates and to improve epidemiological studies when an outbreak occurs. Among the DNA-based genotyping methods, pulsed-field gel electrophoresis (PFGE) is currently used to subtype Salmonella isolates. In this study, the feasibility of genotyping Salmonella enterica serotype Infantis strains using Xba I restriction enzyme was evaluated. Separation of restricted fragments was performed by PFGE. Methods: To test the possibility of applying this methodology to epidemiological investigation, a collection of 26 Salmonella Infantis strains were tested for their susceptibility to 14 antimicrobial agents and were analysed by Xba I macrorestriction followed by PFGE. Detection of class 1 integrons as well as intI1 and bla TEM genes in resistant strains was also studied. Results: Antimicrobial susceptibility testing showed that 84.6% (22/26) of Salmonella Infantis isolates were susceptible to all of the antimicrobials tested, whereas 7.7% (2/26) had low-level resistance to β-lactams and harboured the bla TEM gene. A class 1 integron (0.8 kb) and the intI1 gene (898 bp) were detected in one Salmonella Infantis strain. However, five different PFGE profiles were defined by Xba I macrorestriction. Conclusions: The PFGE method demonstrated adequate typing ability and represents a powerful tool to discriminate the serotype Salmonella Infantis.